(untitled) (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional De Tecnología, Ciencia Y Sociedad, 2022)
Would it be possible – we ask – that a cybernetic-informational system – a computer, android or robot – could come to have self-awareness, that is, to experience awareness of the world around it and also of itself? The objective of this essay is to critically reflect on the current condition of our most modern artificial intelligence (AI) systems, their latent potentials, their promising technical possibilities, but also on their intrinsic structural and functional limitations. To do so, we will take as a case study this time Google’s new LaMDA, which is a powerful expert system for processing spoken human language based on artificial intelligence (AI).